Honokiol/Magnolol-Loaded Self-Assembling Lecithin-Based Mixed Polymeric Micelles (lbMPMs) for Improving Solubility to Enhance Oral Bioavailability - Lin, Hong-Liang; Cheng, Wen-Ting; Chen, Ling-Chun; Ho, Hsiu-O; Lin, Shyr-Yi; Hsieh, Chien-Ming (International journal of nanomedicine, 2021)
This study was intended to utilize lecithin-based mixed polymeric micelles ( MPMs) for enhancing the solubility and bioavailability of honokiol and magnolol to resolve the hindrance of their extreme hydrophobicity on the clinical applications. Lecithin was selected to increase the volume of the core of MPMs, thereby providing a greater solubilization capacity. A series of amphiphilic polymers (sodium deoxycholate [NaDOC], Cremophor and Pluronic series) were included with lecithin for screening and optimization. After preliminary evaluation and subsequentially optimization, two MPMs formulations composed of honokiol/magnolol:lecithin:NaDOC ( MPMs[NaDOC]) and honokiol/magnolol:lecithin:PP123 ( MPMs[PP123]) in respective ratios of 6:2:5 and 1:1:10 were optimally obtained with the mean particle sizes of 80-150 nm, encapsulation efficacy (EEs) of >90%, and drug loading (DL) of >9.0%. These MPMs efficiently stabilized honokiol/magnolol in phosphate-buffered saline (PBS) at room temperature or 4 °C and in fetal bovine serum or PBS at 37 °C. PK study demonstrated that MPMs[NaDOC] showed much improvement in enhancing bioavailability than that by MPMs[PP123] for both honokiol and magnolol. The absolute bioavailability for honokiol and magnolol after intravenous administration of MPMs[NaDOC] exhibited 0.93- and 3.4-fold increases, respectively, compared to that of free honokiol and magnolol. For oral administration with MPMs[NaDOC], the absolute bioavailability of honokiol was 4.8%, and the absolute and relative bioavailability of magnolol were 20.1% and 2.9-fold increase, respectively. Overall, honokiol/magnolol loaded in MPMs[NaDOC] showed an improvement of solubility with suitable physical characteristics leading to enhance honokiol and magnolol bioavailability and facilitating their wider application as therapeutic agents for treating human disorders.